NMNAT1 variants cause cone and cone-rod dystrophy. (March 2018) - Nash, Benjamin; Symes, Richard; Goel, Himanshu; Dinger, Marcel; Bennetts, Bruce; Grigg, John; Jamieson, Robyn
Abstract Cone and cone-rod dystrophies (CD and CRD, respectively) are degenerative retinal diseases that predominantly affect the cone photoreceptors. The underlying disease gene is not known in approximately 75% of autosomal recessive cases. Variants inNMNAT1 cause a severe, early-onset retinal dystrophy called Leber congenital amaurosis (LCA). We report two patients where clinical phenotyping indicated diagnoses of CD and CRD, respectively.NMNAT1 variants were identified, with Case 1 showing an extremely rare homozygous variant c.[271G > A] p.(Glu91Lys) and Case 2 compound heterozygous variants c.[53 A > G];[769G > A] p.(Asn18Ser);(Glu257Lys). The detailed variant analysis, in combination with the observation of an associated macular atrophy phenotype, indicated that these variants were disease-causing. This report demonstrates that the variants inNMNAT1 may cause CD or CRD associated with macular atrophy. Genetic investigations of the patients with CD or CRD should includeNMNAT1 in the genes examined.